IMPLEMENTASI APLIKASI GAME TRIVIA CODING C# DENGAN METODE GDLC BERBASIS ANDROID - Winsen, Winsen; Hutabri, Ellbert (LPPM Universitas Putera Batam, 2023)
This game was developed due to the lack of game-based C# learning media and Indonesian language. The goal of developing this game is to increase Indonesian-based C# coding learning media and improve user skills in C# coding. The design of this game uses the GDLC method which has seven stages, namely Initiation, Team Building, Pre-Production, Main Production, Alpha Version, Beta Version and Release Version. This study also uses UML to describe how this game works, namely Use Case Diagrams, Activity Diagrams, Sequence Diagrams and Class Diagrams. Researcher use Unity and Visual Studio Code to design this game. The result of this research is an Android-based C# coding trivia game. The testing results is this game functions as desired.